Lateglacial and Holocene paleoceanography of the central Nordic Seas - Telesiński, Maciej Mateusz (2014)
Five sediment cores of millennial to multicentennial resolution from the Greenland and Lofoten basins, central Nordic Seas, were analyzed for planktic foraminiferal fauna, planktic and benthic stable oxygen and carbon isotopes, and ice-rafted debris. The Nordic Seas are an important region for the global oceanic system because they constitute the main surface and the only deep water connection between the Artic and North Atlantic oceans. They are also a crucial area for deepwater formation. However, due to a lack of high resolution sediment records the paleoceanography of their central part has been poorly investigated in close detail yet. The results in this report show that on a larger spatial and temporal scale the oceanographic evolution of the Nordic Seas is governed mainly by orbital forcing, but other processes can play an equally important role in shorter-scale, more local changes. The most important of these factors are the intensity of Polar and Atlantic waters inflow, the influence of freshwater discharges, sea-ice processes and deep convection. The circum-Nordic Seas marine-based ice sheets collapsed 18,000-16,000 years before present, releasing large amounts of icebergs and freshwater, which affected the overturning circulation and contributed to the Heinrich stadial 1. Between 12,800 and 11,700 years before present the central Nordic Seas were affected by the last major freshwater outburst related with the Younger Dryas. Most likely it entered the area through the Fram Strait, suggesting an Arctic origin for the trigger of this cold event. The Holocene Thermal Maximum in the central Nordic Seas was delayed compared to their eastern part and stretched well into the middle Holocene. The deep convection, developing in the Greenland Basin since the early Holocene, reached its maximum intensity 7,000-6,000 years before present. Neoglacial cooling increased the stratification of the water column and around 3,000 years before present it led to a drop in the deepwater production rate. Ca. 2,000 years ...